Intimate Friendship and Self Disclosure on Early Adult Instagram Second Account Users - Jati, Puri Puspita; Mardi Rahayu, Maria Nugraheni (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The phenomenon of the second Instagram account is a place to express themselves freely about the thoughts and feelings of the second account user to his close friends. The existence of a second Instagram account allows users to self-disclose to their close friends or who have intimate friendships. The purpose of this study was to determine the relationship between intimate friendship and self-disclosure in early adult Instagram account users. This research is quantitative research with a correlation approach. The sampling technique used is incidental sampling. The sample in the study was 126 uses of Instagram's second account. The method used to retrieve data is incidental sampling technique. The analysis in this study is spearman correlation analysis. Based on the results of the spearman hypothesis test between the intimate friendship variable and self-disclosure showed a correlation coefficient value of 0.339 with a significance of 0.000 (p < 0.05) so that it can be concluded that there is a significant positive relationship between intimate friendship and self-disclosure in early adult Instagram account users. The higher the intimate friendship that the user of the second Instagram account has, the higher the self-disclosure carried out by the user of the second Instagram account in me. Therefore, the second account user self-disclosure of his own information to followers in the second account who have an intimate friendship relationship, namely friends. Based on the results of the spearman hypothesis test between the intimate friendship variable and self-disclosure, it shows that the value of the correlation coefficient is 0.339 with a significance of 0.000 (p<0.05), so it can be concluded that there is a significant positive relationship between intimate friendship and self-disclosure in early adult Instagram account users. The higher the intimate friendship owned by the user of the second Instagram account, the higher the self-disclosure carried out by the user of the second Instagram account on the account.Fenomena akun kedua Instagram merupakan wadah untuk mengekspresikan diri secara bebas mengenai pemikiran dan perasaan pengguna akun kedua kepada teman-teman dekatnya. Adanya akun kedua Instagram memungkin pengguna melakukan self disclosure kepada teman dekatnya atau yang memiliki hubungan intimate friendship. Tujuan dari penelitian ini untuk mengetahui hubungan antara intimate friendship dengan self disclosure pada pengguna akun kedua Instagram dewasa awal. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan korelasi. Teknik sampling yang digunakan yaitu incidental sampling. Sampel dalam penelitian ini adalah 126 penggunaan akun kedua Instagram. Metode yang digunakan untuk mengambil data yaitu teknik incidental sampling. Analisis yang dalam penelitian ini adalah analisis korelasi spearman. Berdasarkan hasil uji hipotesis spearman antara variabel intimate friendship dengan self disclosure menunjukan nilai koefisien korelasi 0.339 dengan signifikansi 0.000 (p<0.05) sehingga dapat disimpulkan terdapat hubungan positif yang signifikan antara intimate friendship dengan self disclosure pada pengguna akun kedua Instagram dewasa awal. Semakin tinggi intimate friendship yang dimiliki pengguna akun kedua Instagram maka semakin tinggi juga self disclosure yang dilakukan pengguna akun kedua Instagram di aku. Oleh karena itu, pengguna akun kedua melakukan self disclosure mengenai informasi dirinya sendiri kepada pengikut di akun kedua yang memiliki hubungan intimate friendship yaitu sahabat. Berdasarkan hasil uji hipotesis spearman antara variabel intimate friendship dengan self disclosure menunjukan bahwa nilai koefisien korelasi 0.339 dengan signifikansi 0.000 (p<0.05) sehingga dapat disimpulkan bahwa ada hubungan positif yang signifikan antara intimate friendship dengan self disclosure pada pengguna akun kedua Instagram dewasa awal.Semakin tinggi intimate friendship yang dimiliki pengguna akun kedua Instagram maka semakin tinggi juga self disclosure yang dilakukan pengguna akun kedua Instagram di akun.